Bactericides Properties of Chitosan Metal Quantum Dots Microbial Pathogenicity Against E. coli, S. aureus, and S. Typhi - Galo Cárdenas-Triviño; María J. Saludes-Betanzo; Luis Vergara-González (International Journal of Polymer Science)
The nanotechnology is considered as a tool to overcome antibiotic-resistant infections. The aim of this study was to investigate the antibacterial properties of quantum dots (QDs) of Au, Ag, and Cu supported in chitosan against Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 29213), and Salmonella Typhi (ATCC 9993) strains. The QDs were synthesized by the method (Chemical Liquid Deposition, CLD) using 2-ethoxyethanol as solvent (1×10−3 M approximate dispersion concentration). Then, NPs supported in chitosan were synthesized by solvated metal atom dispersion (SMAD) in two concentrations, labelled [A] and [B] (0.05 and 0.1 g/L) for each metal with chitosan resulting in an average size of Au 10±2.0, Ag 6±1.3, and Cu 10±2.4 nm, respectively. Several other techniques were performed such as TEM, SEM/EDX, TGA, DSC, and FT-IR for characterizing QDs. The antibacterial assay was performed with 8 agents on cultures of E. coli, S. aureus, and S. Typhi by disk diffusion, broth macrodilution, and determining death curve to the most sensitive pathogen. The antibacterial effect of the nanoparticles was compared using the diameter of growth inhibition zone by agar disk diffusion and through the minimal inhibitory concentration (MIC) and minimal bactericide concentration (MBC) obtained by macrodilution in batch culture with an initial inoculum of 5×105 CFU/mL. The highest bactericidal effect was obtained with nanoparticles of Au, Ag, and Cu (0.1 g/L) with MIC and MBC of 200 and 400 mg/mL, respectively. The greatest bactericidal effect considering the three pathogens turned out to be Ag QDs (0.05 and 0.1 g/L). A bactericidal effect of metal nanoparticles is affected mainly by the electronegativity, the concentration of nanoparticles, and the bacterial age culture.